Dispersion Makes a Difference – The Solid‐State Structure of Hg[N(SiMe3)2]2. Issue 3 (29th January 2018) - Bresien, Jonas; Hering‐Junghans, Christian; Kumm, Peter; Schulz, Axel; Thomas, Max; Villinger, Alexander
Abstract : The solid‐state structure and Raman spectrum of Wannagat's mercurane, Hg[N(SiMe3 )2 ]2 (1 ), are reported. Crystals were grown from the pure substance by slow cooling to –24 °C. Compound1 crystallizes in the monoclinic space group P 21 / c as discrete monomers, which do not display intermolecular mercurophilic interactions. The molecular structure features a nearly linear N–Hg–N scaffold, while the (Me3 Si)2 N groups are in a staggered conformation with a dihedral angle of 58.3° (average) to each other. This can be attributed to intramolecular dispersion interactions according to DFT calculations. Abstract : Dispersion interactions: The dihedral angle Si1–N1–N2–Si3 in Hg[N(SiMe3 )2 ]2 was thought to be 90°. The single‐crystal structure, however, revealed an angle of 58.3° (average). Quantum chemical calculations support the twisted conformation, when dispersion interactions are respected. The dispersion interactions of the Me3 Si groups have significant influence on the structure.